Deploying Cisco wide area application services - Christner, Joel (Cisco Press, 2010)
Implement advanced WAN optimization, application acceleration, and branch virtualization with Cisco WAAS 4.1 This book brings together all the information you need to design and deploy scalable, transparent application acceleration, WAN optimization, and branch virtualization solutions with dramatically improved Wide Area Application Services (WAAS) 4.1 products from Cisco®. Cisco WAAS insiders Joel Christner, Zach Seils, and Nancy Jin systematically cover new WAAS software enhancements that enable far better performance, simplified workflow, and improved manageability. They introduce powerful new solution components including application-specific acceleration techniques, hardware form factors, and virtualization. They also thoroughly explain recent architectural improvements that provide a solid foundation for future WAAS solutions. The authors begin by reviewing the underlying technologies that comprise today's Cisco WAAS solution. Next, drawing on extensive personal experience, they walk through collecting requirements, designing effective solutions, integrating WAAS into existing networks, and configuring WAAS 4.1 software. This book is replete with real-world implementation examples and case studies- including extensive coverage of network, branch office, and data center integration. One step at a time, you'll learn how to deploy Cisco WAAS in a scalable, transparent, and seamless fashion: one that addresses both your business and technical challenges. Thoroughly understand WAAS 4.1's capabilities, and learn how to use and manage it effectively Understand both the Cisco WAAS appliance and router-integrated network module hardware family Quickly deploy WAAS in lab or production pilot environments to quantify its potential benefits Size, design, and deploy Cisco WAAS for maximum performance and value in your enterprise network Compare and select design options for branch office and data center network integration Deploy the WAAS Central Manager and accelerator WAAS devices Implement centralized authentication, authorization, alarm management, monitoring, and reporting Configure WAN optimization with the Application Traffic Policy Manager Configure, verify, and manage application acceleration Leverage WAAS 4.1's powerful new branch office virtualization capabilities Quickly troubleshoot WAAS problems using Cisco's own best practices This book is part of the Networking Technology Series from Cisco Press®, which offers networking professionals ...
Print version record
Keywords: Wide area networks (Computer networks); Application software -- Development; Réseaux à grande distance (Informatique); Logiciels d'application; Développement; Application software; Development; Electrical & Computer Engineering; Telecommunications; Engineering & Applied Sciences